Quantitative analysis of innovative startups in Russia - B. E. Tokarev (Управление)
The results of study in order to determine the number of annual startup launches in the Russian Federation have been presented in the paper. The author’s review of the retrospective study of this topic showed that despite the interest shown in it, almost no materials are published about quantitative value of new startups in the Russian Federation.Launches of new products of year period were selected for analysis and receiving quantitative indicators. In the course of the study, data on startups with signs of innovation were used. In the course of collecting primary information data from available Internet sources with open access, as well as printed publications with reviews of the current state of the venture industry, reports of research conducted by analytical, consulting and start-up investing organizations were obtained. The state of startups in a number of countries of the world have been analysed in the paper. Quantitative data on the state of startups in Russia in order to compare them with similar indicators of foreign countries also have been obtained. The status situation of innovative startups in Russia has been formed.The research has showed that the official statistics of startups is not kept, b oth in Russia and abroad. The study has showed the contradictory nature of available data for analysis about startup launch industry state in Russia. In the proposed material an estimate of the number of startup launches on basis of official registration statistics for newly opened enterprises has been obtained. The analysis has been carried out and estimates of the number of annual startups on the basis of statistical indicators of innovative implementations have been received. The estimation based on an analogy with the known indicators of one of the country regions has been obtained. The final median estimate of the year quantity of startups for Russian Federation has been formed.